Derivational adverbs with confixes is po-...-omy of East-Slobozhan dialects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the basic principles of derivation, the operation and semantics of adverbs, adjectives formed from the base, pronouns, numerals connected with confixes is po-...-omy (the prefix in-, suffix -th) in the dialects of their lexical meaning, lexical-semantic and syntactic relations; confirmed semantic variants adverbializovany lexeme with contextual, situational and positional features.
Keywords: adverbial word formation; lexical- semantic relations; accentual variation; suffixed models